Use of Sun-Induced Chlorophyll Fluorescence in Linear and Nonlinear Light Use Efficiency Models for Remote Estimation of Plant Photosynthesis Under Stress Conditions - M. Pilar Cendrero-Mateo; Shari Van Wittenberghe; Valero Laparra; Uwe Rascher; Shirley A. Papuga; Guillermo Ponce-Campos; Jose Moreno (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This study assessed the potential of sun-induced chlorophyll fluorescence (SIF) to estimate plant net photosynthesis (Anet) using a series of linear and nonlinear light-use efficiency (LUE) models. These models incorporated chlorophyll content-based vegetation indices as proxies for the fraction of absorbed photosynthetically active radiation (APAR) and nonphotochemical and photochemical quenching-related vegetation indices or reflected radiance based biophysical variables as proxies for LUE. A spectral unmixing technique was employed to retrieve the fluorescence quantum efficiency (FQE) and the flux of photons absorbed by beta-Carotene and xanthophyll pigments (APAR-CarbXan), key drivers of nonphotochemical quenching (NPQ). In this study, the maximum photosystem II efficiency (ΦPSII) ranged from 0.10 to 0.40, indicating a low level of photosynthetic performance under the observed conditions. In these conditions, the NPQ exhibited a high level of activation, which controlled the light reaction energy dissipation pathway and broke the positive linear relationship between photochemistry and fluorescence. Therefore, in this study, linear models incorporating FQE and APAR-CarbXan or their combination with meteorological variables failed to accurately capture the seasonal variations in Anet. However, the inclusion of a nonlinear relationship between LUE and FQE significantly improved model performance, demonstrating the necessity of nonlinear models for accurate SIF-based photosynthesis estimation.